The Impact of Ephemeral Content on Digital Marketing Strategies: Efforts to Increase Consumer Engagement and Trust - Lidya Christina; Syaeful Anas Aklani; Stefanus Eko Prasetyo (P3M Politeknik Negeri Bengkalis, 2025)
This study examines the influence of ephemeral content on consumer engagement and trust by integrating quantitative and qualitative evidence through a sequential explanatory mixed-method approach. Quantitative data were collected from 201 active social media users using validated measurement scales for ephemeral content, engagement, and trust (Cronbach’s α = 0.882). The statistical analysis consists of Pearson correlation, validity testing, and simple regression. Results show that ephemeral content significantly predicts consumer engagement (β = 0.570, p < 0.001; R² = 0.32) and consumer trust (β = 0.620, p < 0.001; R² = 0.38). These R² values indicate moderate explanatory power, consistent with the correlation coefficients. The qualitative phase involved semi-structured interviews with 20 participants to explain the mechanisms underlying the statistical relationships. Thematic analysis reveals three psychological factors that shape consumer responses: (1) real-time urgency that triggers FoMO-driven attention, (2) authenticity generated through minimally edited and spontaneous content, and (3) interactive features that foster a sense of participation. Integration of both datasets shows that ephemeral content is effective not merely because of its temporary nature, but because it combines immediacy, emotional proximity, and interactive cues that enhance perceived credibility.